The impact of using social media: exploring the level of insecurity of active and non-active Instagram users in Indonesia / Pijar Suciati … [et al.] - Suciati, Pijar; Maulidiyanti, Mareta; Nurul Karimah, Futihat; Wan Zainodin, Wan Hartini (Faculty of Communication and Media Studies, 2024)
The use of Instagram is currently on the rise among teenagers, and has affected the psychological aspects of adolescents. This study explores the relationship between social media usage, specifically Instagram, and feelings of insecurity among teenagers, who are active and non-active users in Indonesia. The study aims to provide a nuanced understanding of the relationship between social media use and teenagers insecurity levels. The research is conducted using a qualitative approach, by in-depth interview. Participants consist of four Indonesian teenagers who use Instagram actively and infrequently. Sampling technique is purposive sampling and the data analysed with coding and thematic analysis. The findings of this study challenge the notion that active users are always more insecure than infrequent users. The results indicate that factors such as gender, personality traits, the nature of content consumed, following habits, activity level, use of a second account, and the nature of posted content (private/non-personal photos) have a significant influence on insecurity levels. These findings emphasize the complex nature of social media effects on psychological well-being, highlighting the importance of considering multiple factors beyond mere usage frequency. The outcomes of this research provide valuable insights into the nuanced relationship between social media usage and insecurity among Indonesian users.